Second-line systemic therapy for the treatment of metastatic renal cell cancer. Issue 6 (June 2012) - Kruck, Stephan; Bedke, Jens; Kuczyk, Markus A; Merseburger, Axel S
The discovery of molecular mechanisms driving the progression of renal cell carcinoma (RCC) has led to the development of drugs that target RCC at the molecular level. Inhibition of VEGF-targeting pathways is successful as a front-line treatment in patients with metastatic RCC. In addition, bevacizumab/IFN-α, sunitinib and pazopanib are recommended for first-line use in good- or intermediate-risk patients, whereas temsirolimus is approved for poor-risk patients. Second-line options are valuable as these patients eventually progress. The present review addresses which drug is best in this second-line setting. Options for sequential therapy include tyrosine kinase inhibitor (TKI)–mTOR inhibitor or TKI–TKI sequences. We also address the question of whether sequential therapy with TKIs or the combination of VEGF followed by mTOR inhibition is the best choice for specific patients, and which sequence of TKIs is most beneficial.